Management on phytopathogens and doses of Boron in the soybean crop - Silva, Reiner Pimenta da; Nuñez, Daniel Noe Coaguila (Brazilian Journal of Science, 2023)
Soybean (Glycine max (L.) Merr.) is one of the most economically important crops in the world, and Brazil is the world's largest producer of the grain. Crop productivity is mainly defined by the interaction of the plant with the environment and management, mainly phytosanitary and nutritional management. The culture is demanding in Boron (B), a micronutrient essential for the germination of the pollen grain, the growth of the pollen tube and, consequently, the fertilization of the flower and granulation. Thus, the objective was to evaluate methods of consortium of chemical or biological products for the management of phytopathogens, in function of the doses applied in the desiccation and/or applied posterior supplementation in R1 (beginning of flowering), and its effects in the biometric characteristics of the plant and grain productivity. The experiment was installed under no-tillage system, on the Rio Verdinho Três Barras farm, Rio Verde - GO, from October 2021 to March 2022, with a spacing of 0.45 m using the soybean cultivar 'DM 68i69 IPRO', recommended for the region. The experimental design used was in randomized blocks, in a 2x5 factorial scheme with additional [(2x5) + 1], with four replications. The treatments consist of 2 phytosanitary treatments (seed treatment with chemical products and treatment with biological products) for the control of phytopathogens and 5 doses of B (0; 0.25; 0.50; 0.75 and 1.0 L ha-1) applied in desiccation and/or applied further supplementation in R1. At the end, the biometric data of the plants and the final productivity were evaluated. Data were selected for analysis of variance by the F test (p < 0.05) and as means for models, models by the Tukey test (p < 0.05). Polynomial regression analysis was used for doses. The treatments tested could not have a large plant height, insertion height of the first pod, number of productive nodes, number of plants and number of grains per cow. The absence of Boron in the desiccation and application of 1 L ha-1 in R1 provided the highest number of pods per plant. And, the application of higher Boron doses in desiccation and lower doses in the R1 stage provided higher yields.